Parâmetros urbanísticos aplicados em REURB: o caso do bairro São Lázaro em Oriximiná, Pará - TORRES, Jaqueline Barbosa (2022)
This article consists of a literature review on urban parameters and their interfaces with the urban land regularization legislation in Brazil. The procedures required by Law No. 11,977/2009 and later by Law 13,465/2017, demand compliance with urban and environmental technical aspects, in addition to agreements with the main social actors involved, in view of changing some attributions as part of urban regulations on the occasion the definition of urban projects that became part of the urban land regularization projects (REURB). Thus, the objective of this article is to review the outcomes of the land tenure regularization process from the considerations made by the analysis of the application of urban parameters and comparisons between legislations. For this, it uses the case study of the São Lázaro neighborhood located in the city of Oriximiná, state of Pará, for an analysis of the relationship between urban parameters applied locally and their incidence in the REURB process in development in that city.